Antineutrino-induced charge current quasi-elastic neutral hyperon production in ArgoNeuT - Farooq, Saima (Kansas State University, 2016)
This dissertation presents the first topological study of the charge current quasi-elastic (CCQE) neutral hyperon production induced by antineutrinos in the ArgoNeuT detector, a liquid argon time projection chamber (LArTPC) at Fermilab, using 1.20 × 10²⁰ protons-on- target (POT), in the NuMI beam operating in the low energy antineutrino mode. The total cross section for the CCQE neutral hyperon production is reported at the mean production energy of 3.42 GeV. The event yield in data is consistent with the predicted cross section, σ = 2.7 × 10−40 cm²: σ(CCQE[subscript Λ0+Σ0] ) = (3.7 ± 1.9(stat.) ± 1.5 (sys.)) × 10⁻⁴⁰ cm². The study sets a 90% confidence level (C.L.) upper limit on the total cross section of CCQE neutral hyperon production: σ(CCQE[subscript Λ0+Σ0] ) < 7.3 ×10⁻⁴⁰ cm² at 90% C.L.
Keywords: ArgoNeuT; MicroBooNE; High Energy Physics; Neutrino Physics; Fermilab; Neutrino